Local Wisdom for Economic Development of Coastal Communities and Their Problems - Daud Duli; Maryunani Maryunani; Rachmad Kresna Sakti (International Journal Labs, 2023)
This study analyzed forms of local wisdom in Lamalera on whaling, the role of the Lamalera locals in whaling, factors influencing Lamalera locals in whaling and, the consequences and solutions to the factors that influence the Lamalera community in whaling. The researchers used the ethnographic approach and the Sustainable Levelihood Approach (SLA). The results showed that the form of local wisdom in whaling, namely the whaling tradition (Leva Nuang) became a life strategy for the Lamalera community in the form of local wisdom which was marked by the activities of the fishing process, traditional whaling management processes and markets barter. the whaling tradition is a customary tradition that is still maintained to this day. Factors triggering the Lamalera community to carry out whaling activities, namely social capital, namely building harmonious family relationships between fellow Lamalera communities, even with mountain communities, the role of traditional institutions and religious institutions. The Lamalera people also believe that there is land and sea relations and customary norms that become the basis for the life of the Lamalera people in the sea, namely: Prohibition to catch pregnant whales, prohibition to catch blue whales (Klaru), whales must be respected, not allowed to continue chasing whales when they find hills or land in the middle of the sea, and in the sea the fishermen must look at the cardinal directions, if the sun sets the fish being chased must be released. (4) sometimes the Lamalera fishing community ignores this, such as when the community catches pregnant whales.